2020
DOI: 10.1001/jamaoncol.2019.4587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation With Marine ω-3 Fatty Acid on Risk of Colorectal Adenomas and Serrated Polyps in the US General Population

Abstract: Marine ω-3 fatty acid has been suggested to protect against colorectal cancer.OBJECTIVE To assess the effect of daily marine ω-3 fatty acid supplementation on the risk of colorectal cancer precursors, including conventional adenomas and serrated polyps. DESIGN, SETTING, AND PARTICIPANTSThis study was a prespecified ancillary study of the placebo-controlled randomized clinical trial VITAL . An intention-to-treat analysis was used to examine the effect of daily marine ω-3 supplements among 25 871 adults in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…Consistent with our findings, several other large prospective studies did not find any association between PUFAs and CRC risk 34‐36 . Recently, a randomized controlled trial study showed that supplementation with marine n−3 PUFA at 1 g/d was not associated with reduced risk of conventional adenomas or serrated polyps in average‐risk US adults 16 . Several previous studies have examined biomarkers of PUFAs in relation to colorectal neoplasm risk.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our findings, several other large prospective studies did not find any association between PUFAs and CRC risk 34‐36 . Recently, a randomized controlled trial study showed that supplementation with marine n−3 PUFA at 1 g/d was not associated with reduced risk of conventional adenomas or serrated polyps in average‐risk US adults 16 . Several previous studies have examined biomarkers of PUFAs in relation to colorectal neoplasm risk.…”
Section: Discussionsupporting
confidence: 91%
“…[34][35][36] Recently, a randomized controlled trial study showed that supplementation with marine n−3 PUFA at 1 g/d was not associated with reduced risk of conventional adenomas or serrated polyps in averagerisk US adults. 16 Several previous studies have examined biomarkers of PUFAs in relation to colorectal neoplasm risk. Most of these studies assessed plasma PUFAs, which are more susceptible to fasting status and may only reflect dietary intake over several days to weeks compared to erythrocyte PUFAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomised trials have failed to detect a benefit of vitamin D supplementation, alone or combined with calcium, on cancer risk at either high or low doses2539 despite some evidence suggesting reduced total cancer mortality 2540. The limited evidence on fish oil supplementation suggests it does not reduce cancer risk 2841…”
Section: Do Supplements Protect Against Non-communicable Diseases?mentioning
confidence: 99%